Possible legal framework to pioneer Islamic banking in the Maldives: lessons to learn from Malaysia - Wisham, Ismail; Muneeza, Aishath; Hassan, Rusni (LexisNexis Malaysia Sdn Bhd, 2011)
The Maldives has been striving to pioneer Islamic banking for the past few years. For a starter, guidance from the emperor of Islamic banking would be indispensable. Malaysia is the emperor of it. Starting from 1983, it has been practicing Islamic banking up until now. Today, by gradually correcting the mistakes that has been made over the years, Malaysia has become the leading nation for Islamic banking. Malaysia is a multi-religious society, distinct from the Maldives. The point that should be noted here is that when Malaysia started Islamic banking, the only piece of banking legislation available in the country was one that supported the conventional banks. Hence it had to pave away the legal impossibility of introducing Islamic banking to the country by enacting a unique legislation for it. With this new legislation, the first Islamic bank of the country was established. When the government felt that Islamic banking can only be developed by creating more players in the market, it amended the existing conventional banking legislation to allow Islamic banking windows to be operated within conventional banks. The banks began to work in a competitive atmosphere; it gradually developed and the industry has now flourished. The Maldives is a 100% a Muslim nation. However, the existing legal framework is only the operation of conventional banks. Like Malaysia, the Maldives needs to introduce a separate legislation to surface the way to start the Islamic banking. It needs to innovate products according to the need of its society. It also needs to find ways in which it can offer Islamic banking services in a competitive ambiance. If a single bank monopolises the whole industry, the growth of Islamic banking in the Maldives might be jeopardised. Like Malaysia, the Maldives may amend its conventional banking legislations and allow foreign banks like the HSBC Bank to open Islammic banking windows in the country. This would indeed create antagonism in the industry. The citizens would be given an option to choose from and this would create room for the innovation of new products. In this paper, the main focus would be on discussing the possible ways in which to set up and expand Islamic banking in the Maldives with special reference to the expansion of Islamic banking in Malaysia. The development of Islamic banking and the lessons which could be learnt from Malaysia would be highlighted. It is argued here that although Malaysia has a multi-religious society in which Islamic banking was introduced in the 20th CEntury, the Maldives, on the other hand, which is a hundred percent a Muslim nation, is trying to pioneer Islamic banking in the 21st Century and may have lessons to learn from Malaysia's experience.